Characterisation of progenitor cells in human atherosclerotic vessels - Torsney, E; Mandal, K; Halliday, A; Jahangiri, M; Xu, Q (Elsevier, 2006)
Recent data from animal models has demonstrated that both endothelial and smooth muscle progenitor cells contribute to the development of atherosclerosis. However, no data exists concerning the presence of progenitor cells in human atherosclerotic vessels. In the present study, a range of normal and atherosclerotic human arteries were collected from patients undergoing coronary artery bypass surgery. Segments of internal mammary artery (normal controls), and segments of proximal ascending aorta with visible fatty streak were analysed. Immunofluorescence was used to detect a panel of progenitor cell markers. A small number of progenitor cells were identified within neointimal lesions and the adventitia with variable expression of CD34, stem cell antigen (Sca-1), c-kit and VEGF receptor 2 (VEGFR2) markers, but no CD133 expression. On average there was a two- to three-fold increase in progenitor cell number in the adventitia of atherosclerotic vessels compared with normal controls, with a significant difference (p<0.05) in the frequency of cells expressing VEGFR2. Thus, we have provided the first evidence that vascular progenitor cells exist within atherosclerotic lesions, and identified an increased number of progenitor cells in the adventitia of human atherosclerotic vessels. These cells might be a source for smooth muscle cells (SMCs), macrophages and endothelial cells (ECs) that form atherosclerotic lesions.